Konsep-Diri, Kecerdasan Emosi Dan Efikasi-Diri - Yapono, Farid (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2013)
Abstract. The research discusses the relationship of self-concept and emotional intelligence with self-efficacy. The study involved 100 students universities on Jombang East Java to complete scales of Global Self-efficacy (GS-E), self-concept and emotional intelligence. The data results of measurements were analyzed with multiple regression. The analysis showed: 1) there is a positive relationship between self-concept and emotional intelligence with self-efficacy, 2) there was no relationship between self-concept with self-efficacy, and 3) there is positive correlation between emotional inteligence with self-efficacy. Good development of emotional intelligence would increased of self-efficacy. The research findings are discussed in the perspective of developmental tasks of end adolescent.Keywords: self-efficacy, self-concept, emotional intelligence